Análisis, diseño, desarrollo e implementación de una plataforma de video conferencia sobre herramientas libres para la Superintendencia de Control del Poder de Mercado - Alvarez Andrade, Edwin Ramiro (2016)
The Superintendency of Control of Market Power (SCPM) needs to make video communications between one or more users and reduce costs associated as video system license, software license, hardware license, maintenance cost of the videoconferencing system. Currently, the SCPM has a Polycom system, it has presented a high cost. The present study proposes the implementation of a prototype platform videoconferencing for point to point and multipoint using free software. Using the spiral methodology the prototype was developed using open source OpenMeetings, which allows multicalls, point to point, multipoint point, under Ubuntu Linux in a virtualized server within the VShape Client platform. The requirements requested by the SCPM were fulfilled 100%